The Administration of Orange Sweet Potato (Ipomoea Batatas L.) Extract Increases Sperm Consentration, Mortility and Viability in Male Mice Exposed to Cigarette Smoke - Rizqy, Lintang Laila; Nida, Nor Anisatun; Noviana, Dwi Ayu; Nasihun, Taufiqurrachman; Widayati, Eni (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2017)
Introduction: Ipomoea batatas L (LIP) contains antioxidants beta-carotene, vitamin C and vitamin E. Cigarette smoke containing ROS has been proven to decrease sperm quality.Objective: this study aimed to confirm that orange sweet potato extract increases sperm consentration, motility, and viability in mice exposed to cigarette smoke.Methods: In this experimental study with post test only control group design, 30 male mice were divided into 6 groups. Normal group (Nor-G), no intervention, served as the normal control group. Negative control group (Neg-G) was only exposed to cigarette smoke. Positive control group was only treated with IPL 16mg/ml. IPL-15, IPL-16, and IPL-17 group were treated with IPL 15, 16, and 17mg/ml and exposed to cigarette smoke, respectively.Results: Post Hoc LSD analysis showed that means of sperm concentration and viability in IPL-15, IPL-16, and IPL-17 group were significantly higher compared to that of Neg-G (p < 0.05) and were lower compared to that of Nor-G and Pos-G (p < 0.05). Mann Whitney analysis indicated that the persentage of sperm motility in IPL-15, IPL-16, and IPL-17, were significant higher compared to that of Neg-G, p < 0.05. Whilst compared to that of Nor-G and Pos-G the persentage of sperm motility in IPL-15, IPL-16, and IPL-17, there was no significant differences, p > 0.05.Conclusion: treatment of IPL capable of increasing sperm concentration, motility, and viability in male mice were exposed to cigarrette smoke.